BS EN IEC/IEEE 62209-3 AMD 1. Measurement procedure for the assessment of specific absorption rate of human exposure to radio frequency fields from hand-held and body-mounted wireless communication devices. Part 3. Vector measurement-based systems (Frequency range of 300 MHz to 6 GHz) (14th February 2023) - British Standards Institution,
No abstract available